PENGARUH STIMULUS TERHADAP PEMEROLEHAN BAHASA - Gumono Gumono (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2011)
The present study was triggered by a variety of aspects in language education which need our urgent attention. One of these aspects is language acquisition that is related to the developmental stages of children. The pre-school phase is a critical period for the development of children. The research reported in this paper aims to determine whether stimulus are significant in language acquisition buaya pre-school children. The theory underlying the research is based on B. F. Skinner’s theory of behaviorism.